Implementasi Pengelolaan Zakat di Aceh - Djawas, Mursyid (Mazahib, 2016)
This article discusses the local provision of Aceh; Qanun No. 7 of 2004 on Zakat Management. Qanun No. 7 of 2004 on Management of Zakat on the managing zakat is an effort to increase and optimize the potential of zakat in Indonesia, which is still far from the expected. Some of the issues discussed in this article are the provisions of Qanun on muzakki (person who obliged to pay zakat), mustahiq (those entitled to receive zakat ), Baitul Mal and Conditions ' uqubat (sanctions against deviations from the zakat). This article studied by using Islamic approach and normative juridical with Â library research. The results show that the discussion in relation to mustahiq zakat, the Qanun has provided a guarantee for people who in Act No. 18 of 2001 established as one of income sources (local revenue). In the provisions of the charity 's Qanun, very clearly stipulated that zakah is only distributed to mustahiq accordance with Shari'ah. This shows that zakat cannot be used for purposes that are not included in one of the senif that has been clearly mentioned in the Qur'an. In relation to sanctions against irregularities of zakat, the existence of this Qanun can be considered as a complement to Law No. 38 of 1999 on Zakat which still has many shortcomings, especially the clauses providing for sanctions for irregularities to the management of zakat. In the Act, the sanctions more set on irregularities for zakat were Qanun zakat management is already include amyl and muzakki. The Qanun is also member of the delegation of authority for management immense charity by Baitul Mal.Â Keywords: Qanun Aceh, zakat management in Indonesia